Group work in primary school - cooperation, collaboration and beyond - Karnøe, Jonatan; Riis, Marianne (Proceedings of the International Conference on Networked Learning, 2026)
Group work is widespread in Danish schools yet recurrently marked by challenges of participation and coordination. Moreover, “group work” is not a single, stable practice but unfolds across instructional configurations with varying interdependence and digital mediation; an issue central to Networked Learning’s focus on evolving connections between learners, tasks, and technologies. Drawing on year-long ethnographic fieldwork in an 8th-grade class, including observations, video and screen recordings, and interviews, the study analyses how students organise contact and manage task complexity in Danish and biology. Building on Strauss’s concept of articulation work, we show that students continuously regulate contact in response to perceived task demands. Cooperation and collaboration emerge not as fixed categories but as fluid organisational modes through which students balance dependency, workload, and coordination. The analysis also identifies two additional forms that exceed this distinction. In codistribution, responsibility is shared yet differentiated, allowing subsets of a group to collaborate closely while maintaining looser cooperative alignment across the subgroups. In copresence, students work side by side within a shared social frame while primarily engaging in individual task completion, drawing on peers only intermittently. Together, collaboration, cooperation, codistribution, and copresence constitute the Co-4 model. The model conceptualises group work as a dynamic balancing of contact and complexity and offers a refined analytical lens for understanding networked learning processes in classroom practice.